The Lived Experience of a Non-Muslim Chinese in Indonesia's Sharia-Regulated Province of Aceh: A Phenomenological Study - Anwar Abdullah; Saiful Bahri; Zamzami Zainuddin; Taufik Gunawan (Sunan Kalijaga: International Journal of Islamic Civilization, 2021)
This study aims to picture intergroup relationships between Muslim Acehnese and non-Muslim Chinese communities in the Peunayong-regulated province Aceh, Indonesia. A descriptive phenomenological case study methodology was employed to examine the lived experiences of a particular group of people, and at the same time to explore a particular place in Aceh called Peunayong or Chinatown, and the life of its communities. The qualitative research approach was employed in collecting the data through observations, personal interviews, and documents analysis. Phenomenological interviews were conducted from one Muslim Acehnese and one non-Muslim Chinese who have been living for a long period in Peunayong district. Three main themes were merged and discussed in the findings, namely: (a) Peunayong as the symbol of tolerance; (b) non-Muslim and the Sharia law; and (c) discrimination in the Sharia law. In general, despite the implementation of Sharia law, Aceh has been seen as tolerant since Islamic law is limited only to the Muslim population. The portrait of harmony, tolerance, and peace in social-civic between Muslim Acehnese and Non-Muslim Chinese can be witnessed around Peunayong district, either activity related to trading or business, mores, and culture. Meanwhile, this study suggests that the implementation of Sharia law in Aceh should not only to achieve the popular name of “The Veranda of Mecca” or as a symbol and a name, or for political purposes, but its implementation should provide a welfare impact to local communities including Muslim and non-Muslim alliances, also to support religious freedom and solidarity between religious communities.